1975
DOI: 10.3323/jcorr1974.24.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alloying Elements on the Pitting Corrosion of Stainless Steels

Abstract: Effects of alloying elements on the pitting corrosion resistance of 17Cr-16Ni steels with and without 4% Mo were evaluated by the corrosion rate in 10% FeCl3.6H2O and 4% NaCl added with hydrogen peroxide and by the polarization measurement in 0.1N NaCl+0.1-0.25N Na2SO4 at 40C.The elements, the content of which was varied, were carbon, nitrogen, silicon, phosphorus, sulfur, manganese and nickel. The supplementary alloying elements were aluminum, titanium, vanadium, cobalt, copper, zirconium, niobium, tin and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
2
17
0
2
Order By: Relevance
“…11,12) Suter and Böhni 13) confirmed that the pitting potential depends on the size of inclusions, and that this size has to be kept well below 1 µm in order to substantially improve the pitting resistance of stainless steels. This assumption is in good agreement with the observations reported many years ago by Osozawa et al, 14) in which stable pitting corrosion pit growth was not observed in stainless steels with inclusions of no more than 2.5 µm in size.…”
Section: )supporting
confidence: 82%
“…11,12) Suter and Böhni 13) confirmed that the pitting potential depends on the size of inclusions, and that this size has to be kept well below 1 µm in order to substantially improve the pitting resistance of stainless steels. This assumption is in good agreement with the observations reported many years ago by Osozawa et al, 14) in which stable pitting corrosion pit growth was not observed in stainless steels with inclusions of no more than 2.5 µm in size.…”
Section: )supporting
confidence: 82%
“…[1][2][3][4][5][6] Compared to other additives such as chromium or molybdenum, a minute nitrogen content is effective in improving resistance to localized corrosion. Moreover, nitrogen addition helps to refine the microstructure and increase the strength of the material, and it can be used instead of nickel as an austeniteforming element.…”
Section: Introductionmentioning
confidence: 99%
“…At relatively low potentials, solidified nitrogen dissolves with crevice corrosion to produce NH 4 þ in the solution and control the acidification inside the pit. 2) In the present research, increase of the nitrogen content in nitrogen-bearing austenitic steel results in (1) decreased of number of crevice corrosion spots and the corrosion weight loss, with a tendency to further decrease as the polarization potential reaches high values; (2) the amount of NO 3 À eluted into the solution showed a tendency to increase, and at the same time, the eluted NO 3 À was adsorbed onto the surface of the passivation film, which had a inhibitor effect suppressing the dissolution of the base metal; (3) the peak current density and the total quantity of electricity for the repassivation process decreased and indicated a high corrosion resistance which promotes repassivation.…”
mentioning
confidence: 99%
“…[1][2][3][4] Many authors have investigated corrosion property of nitrogen added stainless steels and recognized that nitrogen improves corrosion resistance especially for localized one. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pitting, the most typical form of localized corrosion, is a crucial issue for passivating materials in practical use.…”
Section: Introductionmentioning
confidence: 99%